Gender Differences in Tackling Fake News: Different Degrees of Concern, but Same Problems - Almenar, Ester (2021)
In the current media ecosystem, in which the traditional media coexists with new players who are able to produce information and spread it widely, there is growing concern about the increasing prominence of fake news. Despite some significant efforts to determine the effects of misinformation, the results are so far inconclusive. Previous research has sought to analyze how the public perceive the effects of disinformation. This article is set in this context, and its main objective is to investigate users’ perception of fake news, as well as identify the criteria on which their recognition strategies are based. The research pays particular attention to determining whether there are gender differences in the concern about the effects of fake news, the degree of difficulty in detecting fake news and the most common topics it covers. The results are based on the analysis of a representative survey of the Spanish population (N = 1,001) where participants were asked about their relationship with fake news and their competence in determining the veracity of the information, and their ability to identify false content were assessed. The findings show that men and women’s perception of difficulty in identifying fake news is similar, while women are more concerned than men about the pernicious effects of misinformation on society. Gender differences are also found in the topics of the false information received. A greater proportion of men receive false news on political issues, while women tend to more frequently receive fake news about celebrities.